STUDI FENOMENOLOGI MAKNA TRADISI BATING BAGI WARGA JEMAAT GEREJA TORAJA JEMAAT MORIA KATA KLASIS MALIMBONG - Gusti Somalinggi’ (ADISAM PUBLISHER, 2023)
A Phenomenological Study of the Meaning of the Bating Tradition for the Toraja Church Congregation, the Moria Congregation, Kata Klasis Malimbong